Pemanfaatan Daun Singkong Menjadi Keripik Daun Singkong (Crantz) di Desa Larangan Luar Kecamatan Larangan Kabupaten Pamekasan - Dzikri Wahyu Ramadhani; Conny Dian Sumadi; M. Saufi Rahman (BEKTI : Jurnal Pengabdian kepada Masyarakat, 2024)
Crantz is a product made from cassava leaves that has been innovated to have a higher selling value. This community service (KKNT) was conducted in Larangan Luar Village, Larangan Subdistrict, Pamekasan with the aim of increasing the knowledge and skills of villagers in making cassva leaf chips (Crantz). The method used was demonstration and experimentation, namely giving theory and simulation to target participants, followed by the practice of making cassava leaf chips (Crantz). Based on the results of observations of the participants' responses from the beginning to the end of the service activities, the cassava leaf chips (Crantz) making training succeeded in increasing the knowledge and skills of villagers in Larangan Luar Village especially around Taneyan Lanjhang Heritage, Buddagan 1.